2020
DOI: 10.1186/s12936-020-03222-8
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining LLIN coverage with continuous distribution: the school net programme in Tanzania

Abstract: Most malaria-endemic countries have struggled in the past decade to establish effective national-scale continuous distribution mechanisms for long-lasting insecticidal nets (LLINs). Since the implementation of the Tanzania National Voucher Scheme in 2004 and mass-distribution campaigns in 2009-2011 and 2015-2016, Tanzania has been committed to finding new and innovative ways of achieving and maintaining universal bed net coverage. Planning for the School Net Programme (SNP) began in 2011 and in 2013, the count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 17 publications
0
42
1
Order By: Relevance
“…Households in these areas appear more dependent on mass distribution campaigns as the primary source of LLINs. In these more remote communities, school-based distributions may sustain higher and more equitable coverage [16,17,37]. Uganda also has an established network of community health workers, many of whom already perform evaluation and management of uncomplicated malaria, who could be leveraged to identify households without adequate LLINs [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Households in these areas appear more dependent on mass distribution campaigns as the primary source of LLINs. In these more remote communities, school-based distributions may sustain higher and more equitable coverage [16,17,37]. Uganda also has an established network of community health workers, many of whom already perform evaluation and management of uncomplicated malaria, who could be leveraged to identify households without adequate LLINs [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…A much smaller proportion of the existing literature has examined the effectiveness of LLIN distribution outside of mass distribution campaigns, [16][17][18][19][20][21] particularly in regard to geographic factors that may impact the coverage. While analysis of routine DHS data from 25 countries found that facility-based distribution improves LLIN ownership rates and reported use [22] a study in rural Kenya found that increased distance from health facilities was associated with decreased bed net ownership [23] and another a study in Malawi found that households further from health facilities were less likely to own a net and have their child sleep under it [24] Therefore, as part of an ongoing, cross-sectional study of malaria transmission in the western Ugandan highlands, we sought to examine how geographic factors, including elevation and distance to clinic, might influence malaria risk and LLIN use in order to inform future distribution strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficiaries of these products are located mainly in sub-Saharan Africa and South America. In the literature, review articles about the subject [25][26][27] evaluated criteria and strategies for last mile distribution and delivery of bed nets from a distribution point located in the beneficiaries' country.…”
Section: Problem Statement and Contributionmentioning
confidence: 99%
“…Malaria infection varies nationwide with an average prevalence of 7.3% in children under 5 years of age in 2017 [4]. Vector control by the National Malaria Control Programme (NMCP) is based on sustaining high LLIN access and use [5], via universal coverage campaigns supplemented with continuous distribution from school net programmes, antenatal care campaigns and the expanded programme for immunization; and targeted IRS in high transmission areas in the North-West [6]. Effective and sustainable malaria vector control is plagued by a number of challenges, including the evolution of vector behavioural and physiological resistance to current control interventions [7].…”
Section: Introductionmentioning
confidence: 99%